Pengaruh Pola Asuh Orang Tua terhadap Kejadian Stunting Pada Balita di Desa Pong Murung - Centis, Maria Conchita Leyla; Trisnawati, Reineldis E.; Dewi, Imelda Rosniyati; Bandur, Paskalinda M.Y (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Stunting is one of the nutritional problems that is being addressed. Stunting has negative impact on growth and development in toddlers so that it must be resolved immediately must be resolved immediately. The cause of stunting in toddlers is malnutrition for a long period of time a long period of time. Many factors influence the incidence of stuntingone of which is parenting. Parenting patterns are closely related with the fulfillment of child nutrition, for example preparing food and also in providing stimulus to children. providing stimulus to children. To determine the effect of parenting patterns on the incidence of stunting in toddlers. The method used is quantitative with a cross sectional approach. The sample in the study amounted to 79 toddlers. Statistical test used is chi square. The results showed that there was an influence of parenting patterns on the incidence of stunting in toddlers with a p value of 0.03 <0.05. on the incidence of stunting in toddlers with a p value of 0.03 <0.05. Parenting patterns parenting plays an important role in determining the nutritional status of a toddler. So that so that the parenting pattern applied is good parenting, the growth and development of toddlers is more optimal development of toddlers is more optimal Keywords: Parenting, Stunting, Toddlers  ABSTRAK Stunting merupakan salah satu masalah gizi yang sedang diatasi. Stunting memberikan dampak yang negatif bagi pertumbuhan dan perkembang pada balita sehingga harus segara diatasi. Penyebab kejadian stunting pada balita adalah kurang gizi dalam jangka waktu yang cukup lama. Banyak factor yang mempengaruhi kejadian stunting salah sarunya adalah pola asuh orangtua. Pola asuh orang tua berhubungan erat dengan pemenuhan gizi anak yaitu misalnya menyiapkan makanan dan juga dalam memberikan stimulus kepada anak. Untuk mengetahui pengaruh pola asuh orangtua terhadap kejadian stunting pada balita. Metode yang digunakan adalah kuantitatif dengan pendekatan cross sectional. Sampel dalam penelitian berjumlah 79 balita. Uji statistic yang digunakan adalah chi square. Hasil penelitian menunjukkan bahwa ada pengaruh pola asuh orangtua terhadap kejadian stunting pada balita dengan nilai p valuae 0,03 < 0,05. Pola asuh orang tua berperan penting dalam menentukan status gizi seorang balita. Sehingga pola asuh yang diterapkan adalah pola asuh yang baik maka pertumbuhan dan perkembangan balita lebih optimal Kata Kunci: Pola Asuh, Stunting, Balita